A comparative study of hematological profile on presentation in confirmed cases of malaria, dengue and leptospirosis - Vaidya, Meghna Sachin; Kawale, Juhi Balwant; Maheshkar, Parag Rajkumar; Kamble, Aniket Namdev (International Journal of Research in Medical Sciences, 2018)
Background: Malaria, leptospirosis and dengue fever are the predominant monsoon related illnesses in the Indian subcontinent causing considerable mortality and morbidity. These have similar clinical profile and derangement in one or more haematological parameters. We have studied the haematological profile at presentation to differentiate one infection from the other as it presents a significant diagnostic challenge to the treating physician. Methods: A prospective observational study of haematological profile in a total of 336 patients of malaria (plasmodium falciparum, plasmodium vivax and mixed malaria), dengue and leptospirosis were conducted over a period of 1 year in a tertiary care centre in western Maharashtra. Results: In the age group of 20-40 years all the infectious subgroups were observed to have the maximum number of patients with a male preponderance. Maximum frequency of Haemoglobin in leptospirosis was 7-10gm%. Maximum mortality in mixed malaria and leptospirosis was seen with haemoglobin levels <7gm%. In P. vivax malaria, P. falciparum malaria and dengue mortality was not seen in patients with Hb<7gm%. Conclusions: Leucocytosis is most commonly seen in leptospirosis. Patients presenting with leucopenia are most likely to have P. vivax malaria. Mixed malaria was most likely to have thrombocytopenia on presentation. Haemoglobin of <7gm% in leptospirosis and mixed malaria probably predicts a poor outcome.